Relaciones entre la Universidad de Costa Rica y el Museo Nacional: Las pericias de la investigación antropológica costarricense - Bolaños, Margarita (2015)
This article show, in the last six decades, diverse scenarios and actors who were involved in research projects and training programs of Costa Rican anthropologists. It also proposes new elements in order to understand the University of Costa Rica and the National Museum efforts that were made, jointly or separately, since 1940, in order to study and protect the cultural heritage of the Costa Rica Nation.